Glycolytic enzyme HK2 promotes PD-L1 expression and breast cancer cell immune evasion - Lin, Jichun; Fang, Wenshuo; Xiang, Zhuo; Wang, Qingqing; Cheng, Huapeng; Chen, Shimin; Fang, Jing; Liu, Jia; Wang, Qiang; Lu, Zhimin; Ma, Leina (Frontiers in Immunology, 2023)
Immune therapies targeting the PD-1/PD-L1 pathway have been employed in the treatment of breast cancer, which requires aerobic glycolysis to sustain breast cancer cells growth. However, whether PD-L1 expression is regulated by glycolysis in breast cancer cells remains to be further elucidated. Here, we demonstrate that glycolytic enzyme hexokinase 2 (HK2) plays a crucial role in upregulating PD-L1 expression. Under high glucose conditions, HK2 acts as a protein kinase and phosphorylates IκBα at T291 in breast cancer cells, leading to the rapid degradation of IκBα and activation of NF-κB, which enters the nucleus and promotes PD-L1 expression. Immunohistochemistry staining of human breast cancer specimens and bioinformatics analyses reveals a positive correlation between HK2 and PD-L1 expression levels, which are inversely correlated with immune cell infiltration and survival time of breast cancer patients. These findings uncover the intrinsic and instrumental connection between aerobic glycolysis and PD-L1 expression-mediated tumor cell immune evasion and underscore the potential to target the protein kinase activity of HK2 for breast cancer treatment.